Single-molecule FRET reveals multiscale chromatin dynamics modulated by HP1α - Sinan Kilic (Nature Portfolio, 2018)
Chromatin fibers undergo continuous structural rearrangements but their dynamic architecture is poorly understood. Here, the authors use single-molecule FRET to determine the structural states and interconversion kinetics of chromatin fibers, monitoring their effector protein-dependent dynamic motions.